Petroleum-fuelled methanogenesis and microbial hydrocarbon oxidation at an abandoned oil well - Martin Blumenberg; Sebastian Jordan; Georg Scheeder; Martin Krüger; Stefan Schloemer (Applied Geochemistry, 2025)

The control of physical and biological drivers on pelagic methane fluxes in a Patagonian fjord (Golfo Almirante Montt, Chile) - Oliver Schmale; Volker Mohrholz; Svenja Papenmeier; Klaus Jürgens; Martin Blumenberg; Peter Feldens; Sebastian Jordan; Paula Ruiz-Fernández; Christian Meeske; Jenny Fabian; Sören Iwe; Lars Umlauf (Science of The Total Environment, 2025)

Discrepant mass accumulation rates of sediments in the South Pacific Ocean from 230Th and 3He measurements - Frank J. Pavia; Jordan T. Abell; Jennifer L. Middleton; Annie Leal; Sebastian M. Vivancos; Martin Q. Fleisher; Gisela Winckler; Robert F. Anderson (Geochimica et Cosmochimica Acta, 2024)

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

Parentage analysis across age cohorts reveals sex differences in reproductive skew in a group‐living cichlid fish, Neolamprologus multifasciatus - Aneesh P. H. Bose; Johanna Dabernig‐Heinz; Lukas Koch; Jacqueline Grimm; Sebastian Lang; Bernadett Hegedűs; Taylor Banda; Lawrence Makasa; Alex Jordan; Kristina M. Sefc (Molecular Ecology, 2022)
Group‐living animals are often faced with complex reproductive decisions, namely how to partition within‐group reproduction, how to obtain extra‐group reproduction and how these two means of reproduction should be balanced. The solutions to these questions can be difficult to predict because ecological conditions can affect the scopes for within‐group and extra‐group reproduction in complex ways. For example, individuals that are restricted from moving freely around their habitats may have limited extra‐group reproductive opportunities, but at the same time, groups may live in close proximity to one another, which could potentially have the opposite effect. The group‐living cichlid fish Neolamprologus multifasciatus experiences such ecological conditions, and we conducted an intensive genetic parentage analysis to investigate how reproduction is distributed within and among groups for both males and females. We found that cohabiting males live in “high‐skew” societies, where dominant males monopolize the majority of within‐group reproduction, while females live in “low‐skew” societies, where multiple females can produce offspring concurrently. Despite extremely short distances separating groups, we inferred only very low levels of extra‐group reproduction, suggesting that subordinate males have very limited reproductive opportunities. A strength of our parentage analysis lies in its inclusion of individuals that spanned a wide age range, from young fry to adults. We outline the logistical circumstances when very young offspring may not always be accessible to parentage researchers, and present strategies to overcome the challenges of inferring mating patterns from a wide age range of offspring.

Patient and public preferences for being recontacted with updated genomic results: a mixed methods study - Chloe Mighton; Marc Clausen; Agnes Sebastian; Sarah M. Muir; Salma Shickh; Nancy N. Baxter; Adena Scheer; Emily Glogowski; Kasmintan A. Schrader; Kevin E. Thorpe; Theresa H. M. Kim; Jordan Lerner-Ellis; et al. (Human Genetics, 2021)

A New Rapid Method to Assess the Durability of Shale - L. Sebastian Bryson; Jordan S. Kirkendoll; Majid Mahmoodabadi (Geotechnical and Geological Engineering, 2019)

Myositis in Lewis rats induced by the superantigen Staphylococcal enterotoxin A - Alexander Emmer; Abimbola Abobarin-Adeagbo; Andreas Posa; Berit Jordan; Karl-Stefan Delank; Martin Sebastian Staege; Alexander Surov; Stephan Zierz; Malte Erich Kornhuber (Molecular Biology Reports, 2019)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

The Arctic Coastal Dynamics Database: A New Classification Scheme and Statistics on Arctic Permafrost Coastlines - Hugues Lantuit; Pier Paul Overduin; Nicole Couture; Sebastian Wetterich; Felix Aré; David Atkinson; Jerry Brown; Georgy Cherkashov; Dmitry Drozdov; Donald Lawrence Forbes; Allison Graves-Gaylord; Mikhail Grigoriev; et al. (Estuaries and Coasts, 2012)